Changes in hepatic gene expression and serum metabolites after oral administration of overdosed vitamin-E-loaded nanoemulsion in rats. (November 2017) - Park, Chae Young; Jang, Chul Ho; Lee, Do Yup; Cho, Hyung Taek; Kim, Young Jun; Park, Yoo Heon; Imm, Jee-Young
Abstract: Vitamin-E-loaded nanoemulsion (Vit E-NE) was produced, and the effects of repeated oral administration of Vit E-NE (2 g/kg/day) for five days on hepatic gene expression and serum metabolites were investigated in rats. The mean particle diameter and zeta potential of Vit E-NE was 112 nm and 56 mV, respectively. Vit E-NE administered rats showed significantly higher triglyceride content than of standard diet (control) or Vit E control emulsion (Vit E-CE) group but no toxicity symptoms were found in blood biochemical analysis. Next generation sequencing analysis of rat liver revealed that several genes related to energy and xenobiotic metabolism (CYP1A1 and glutathione S-transferase) were significantly altered. Serum metabolites (B-hydroxybutyrate and palmitoleic acid) indicating ketone body production and activation of stearoyl-CoAdesaturase were significantly increased by administration of Vit E-NE. The results of this study suggest that excessive consumption of edible nano-sized food ingredients can possibly cause adverse effects. Highlights: Administration of Vitamin E nanoemulsion (Vit E-NE, 2 g/kg/day 5 days) did not show toxicity in rats. Hepatic gene expressions related to energy and xenobiotic metabolism were up-regulated by administration of Vit E-NE. β -hydroxybutyrate, palmitoleic acid, and oleic acid were significantly increased in serum by administration of Vit E-NE. Excessive consumption of edible nano-sized food ingredients can possibly cause adverse effects. Transcriptomic and metabolomic profiling can be used to identify potential health risks prior to development of diseases.